NOFILOLOGIK YO‘NALISHLARDA CHET TILINI O‘QITISH METODIKASI - To‘xtaboyev Dilshodbek Sobirovich; Maksudova Hilola Ferdinandovna (TADQIQOTLAR, 2026)
This article examines the theoretical and practical foundations of teaching a foreign language to students of non-philological fields. In particular, the effectiveness of professionally oriented foreign language education, the formation of communicative competence, CLIL (Content and Language Integrated Learning) methodology, as well as interactive and innovative teaching methods, are analyzed. In addition, modern approaches to foreign language teaching through the use of information and communication technologies are highlighted.